TWITTER AS A LEARNING MEDIA OF ENGLISH AS A FOREIGN LANGUAGE - Utimadini, Nindya Juwita; ., Sudarsono; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The technology revolution has occurred in the last decade, supported by computer and telecommunication based technologies. O’Reilly (2005), one of the authors of the term, Web 2.0 as a collaborative environment in which users have the opportunity to contribute to a growing knowledge base, assist in the development of web-based tools, and participate in online communities. One of the products is Web 2.0. In the language learning domain, the practice of using Web 2.0 tools has been widespread. Web 2.0 tools, interchangeably named social media or social technologies, are penetrating all aspects of language learning activities. Recently, the immense popularity of social networking websites has created new opportunities for language learners. The present study introduced Twitter, as the form of Web 2.0 application, used as the learning media of English as a Foreign Language. This study involved 5 students as the respondents. The data were obtained from the documented data and the direct observation to the research participants. The finding shows that the students did various activities and got benefits from using Twitter as a media to learn English as a foreign language.   Keywords       : Twitter, language learning media.   Abstrak: Dalam dekade terakhir, revolusi teknologi yang didukung oleh komputer dan telekomunikasi berbasis teknologi. O'Reilly (2005), peneliti Web,20, menyatakan Web 2.0 sebagai sebuah lingkungan kolaboratif yang memberikanpengguna kesempatan untuk berkontribusi dalam mengembangkan pengetahuan, membantu pengembangan media berbasis web, dan berpartisipasi dalam komunitas online. Wujudnya adalah Web 2.0. Dalam pembelajaran bahasa, praktek menggunakan Web 2.0 tools telah tersebar luas. Web 2.0, yang juga disebut sosial media atau teknologi sosial, menembus semua aspek kegiatan belajar bahasa. Baru-baru ini, popularitas situs jaringan sosial telah menciptakan peluang baru untuk belajar bahasa. Tujuan penelitian ini adalah untuk menginvestigasi Twitter, sebagai bentuk aplikasi Web 2.0 yang digunakan sebagai media pembelajaran bahasa Inggris sebagai bahasa asing. Metode yang digunakan adalah studi kasus. Studi ini melibatkan 5 siswa sebagai responden. Data diperoleh dari data yang didokumentasikan dan pengamatan langsung kepada peserta penelitian. Hasil temuan menunjukkan bahwa siswa melakukan berbagai kegiatan dan mendapat manfaat dari menggunakan Twitter sebagai media untuk belajar bahasa Inggris sebagai bahasa asing. Keywords       : Twitter, media pembelajaran bahasa.